Strategi Mahasiswa Dalam Mengatur Penggunaan Gadget dan Belajar Untuk Kesehatan - Sofia, Azyka; Dawamah, Nurazizah (Cindoku : Jurnal Keperawatan dan Ilmu Kesehatan, 2025)
The term “gadget” is used to refer to small electronic devices that serve a specific purpose. In Indonesian, gadgets are often referred to as “gawai”, a term that comes from English and encompasses a variety of devices designed to make human activities easier, such as tablets, smartphones and laptops. Novelty is the hallmark of gadgets, as this technology is constantly updated to meet the needs of users. Gadgets have many benefits, such as easy access to data and communication, but overuse can lead to various health problems.  Gadgets not only serve as communication tools, but they also have the potential to cause addiction that impacts physical and mental health. The purpose of this study was to evaluate the effects of device use on students' health and desire to learn through a literature review. The research method used is an examination of literature from various sources related to the research topic. The results of the analysis show that device use has effects on students' health such as anxiety, stress, and device addiction. In addition, the use of electronic devices has an impact on learning motivation, such as decreased interest and concentration. To overcome these negative effects, a broader approach is needed, such as limiting the time spent using electronic devices, using innovative learning strategies, and improving student engagement.